2019
DOI: 10.3389/fmicb.2019.02435
|View full text |Cite
|
Sign up to set email alerts
|

Putative Mixotrophic Nitrifying-Denitrifying Gammaproteobacteria Implicated in Nitrogen Cycling Within the Ammonia/Oxygen Transition Zone of an Oil Sands Pit Lake

Abstract: Anthropogenically-impacted environments offer the opportunity to discover novel microbial species and metabolisms, which may be undetectable in natural systems. Here, a combined metagenomic and geochemical study in Base Mine Lake, Alberta, Canada, which is the only oil sands end pit lake to date, revealed that nitrification was performed by members from Nitrosomonadaceae, Chloroflexi and unclassified Gammaproteobacteria “MBAE14.” While Nitrosomonadaceae and Chloroflexi groups were relatively abundant in the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 62 publications
1
29
0
1
Order By: Relevance
“…Both Dehalococcoidia and JG30-KF-CM66 are affiliated to Chloroflexi. Meanwhile, the former contains the genes associated with degradation of various organic matter such as fatty acids and aromatic compounds (Wasmund et al, 2014) and the latter contains genes related to nitrite oxidoreduction (Mori et al, 2019). Gemmatimonadetes can be involved in polyphosphate accumulation and carotenoid production in soil (Zhang H. et al, 2003;Takaichi et al, 2010).…”
Section: Network Relationship Among Anmesmentioning
confidence: 99%
“…Both Dehalococcoidia and JG30-KF-CM66 are affiliated to Chloroflexi. Meanwhile, the former contains the genes associated with degradation of various organic matter such as fatty acids and aromatic compounds (Wasmund et al, 2014) and the latter contains genes related to nitrite oxidoreduction (Mori et al, 2019). Gemmatimonadetes can be involved in polyphosphate accumulation and carotenoid production in soil (Zhang H. et al, 2003;Takaichi et al, 2010).…”
Section: Network Relationship Among Anmesmentioning
confidence: 99%
“…The Base Mine Lake is characterized by high concentrations of dissolved methane and ammonia (up to 253 μM and 73.5 μM, respectively; Fig. 1a and see also Supplementary Table 1 ), especially in the hypolimnetic zone (the lower layer of water in a thermally stratified lake) and at the tailings–water interface, reflecting mobilization of these reductants from the underlying tailings 21 , 22 . Stable isotope analysis (d 13 C, d 2 H) of pore water methane from within the tailings indicated that the methane was produced via fermentation by indigenous methanogenic archaea 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the well‐known ammonia oxidizers, Nitrosopumilus and Nitrospina were present at low relative abundances during the first two time points (<4% of total abundance), and they accounted for <1% during the remaining season. Pseudomonadaceae and Nitrincolaceae contain genes for nitrite oxidoreductase (Mori et al ., 2019), mediating the transformation from nitrite to nitrate. Genes for nitrite reductase, nitric oxide reductase and nitrous oxide reductase are further present in Nitrincolaceae (Mori et al ., 2019) indicating their potential to reduce nitrite to nitrous oxide (N 2 O) and dinitrogen (N 2 ).…”
Section: Discussionmentioning
confidence: 99%